Impact of COVID-19 pandemic on the apparel industry; disruptions in demand, supply chain and operations with the strategies to survive. - Ijaz, Taha Bin (2021)
The COVID-19 pandemic is a crisis that challenges everyone everywhere. Apart from serious threats to health and safety of people, it has caused serious impacts on the business activities. This study is aimed at finding the impact of COVID-19 on the apparel industry. The study includes the challenges that the apparel companies faced during the pandemic and how they came up with different strategies to survive during the pandemic. After reviewing the literature, findings are listed which are gathered by in-depth semi-structured interviews of owners of small-scale apparel companies which is followed by an extensive analysis that discuss the severity of challenges and the effectiveness of strategies adapted by the apparel companies. This study has the potential to act as a guide for business owners or managers of apparel businesses apart from the academics.